Determinants of Non-Performing Financing Islamic Finance Bank (BPRS) in Indonesia - Minoto, Minoto (El-Qish: Journal of Islamic Economics, 2023)
This study aims to empirically test the determinants or factors that affect Non- Performing Finance (NPF) in Islamic Finance Banks (BPRS) in Indonesia. The determinants analyzed are internal and external factors. Internal factors consist of the Capital Adequacy Ratio (CAR), Financing to Deposits Ratio (FDR) and Operating Costs for Operating Income (BOPO). Meanwhile, external factors are inflation, exchange rate and interest rate (BI rate). This study uses a quantitative approach. The research data is secondary data obtained from the websites of the Otoritas Jasa Keuangan (OJK) and Bank Indonesia. The data collection technique is through time series data collection from 2013 to 2020. As for data analysis using multiple linear regression analysis. Based on the results of the study showed that simultaneously internal and external factors had an effect on Non-Performing Finance. While some of the internal factors, namely CAR, FDR and BOPO have a positive and significant effect on the NPF. On external factors, the exchange rate variable partially has a positive and significant effect on the NPF, while the BI Rate has a negative and significant effect on the NPF, but the inflation variable partially has no significant effect on the NPF.